2023
DOI: 10.1093/rb/rbad006
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun naringin-loaded microsphere/sucrose acetate isobutyrate system promotes macrophage polarization toward M2 and facilitates osteoporotic bone defect repair

Abstract: Repairing osteoporotic bone defects is still a major clinical challenge. Recent studies have revealed that immune response is also essential in osteogenesis. The intrinsic inflammatory response of the host, especially the M1/M2 polarization status and inflammatory secretory function of macrophages, can directly affect the osteogenic differentiation. Therefore, in this study, an electrospun naringin-loaded microspheres/sucrose acetate isobutyrate (Ng-m-SAIB) system was constructed to investigate its effect on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…In addition, it was reported that the anti-inflammatory effects of NG are regulated by multiple mechanisms including (1) the promotion of macrophage M2 polarization through PI3K/AKT/mTOR signaling pathways; (2) inhibition of multiple inflammation-related signaling pathways (such as NF-κB and MAPK pathways) to reduce the production of inflammation-related factors, thereby suppressing inflammation, and (3) adjustment of the peroxisome proliferator-activated receptor (PPAR)/miR-21 pathway participating in the regulation of inflammation. 46–49…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it was reported that the anti-inflammatory effects of NG are regulated by multiple mechanisms including (1) the promotion of macrophage M2 polarization through PI3K/AKT/mTOR signaling pathways; (2) inhibition of multiple inflammation-related signaling pathways (such as NF-κB and MAPK pathways) to reduce the production of inflammation-related factors, thereby suppressing inflammation, and (3) adjustment of the peroxisome proliferator-activated receptor (PPAR)/miR-21 pathway participating in the regulation of inflammation. 46–49…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it was reported that the anti-inflammatory effects of NG are regulated by multiple mechanisms including (1) the promotion of macrophage M2 polarization through PI3K/AKT/ mTOR signaling pathways; (2) inhibition of multiple inflammation-related signaling pathways (such as NF-kB and MAPK pathways) to reduce the production of inflammation-related factors, thereby suppressing inflammation, and (3) adjustment of the peroxisome proliferator-activated receptor (PPAR)/miR-21 pathway participating in the regulation of inflammation. [46][47][48][49] Bone regeneration involves three successive phases in the induction of new bone regeneration: inflammation, repair, and remodeling phases. As shown in earlier research, prolonged chronic inflammation caused by macrophages of M1 type could induce the absorption of bone tissue, which causes the formation of a fibrous envelope, blocks the combination of bone cells and implants, and ultimately leads to the failure of bone repair.…”
Section: Osteogenic Differentiation Of Mbmscs In the Macrophage-condi...mentioning
confidence: 99%
“…Next, the marker genes related to osteogenesis differentiation were detected by Q-PCR analysis in BMSCs cultured on pBMP2 incorporated DAM-coated Ti surface for 3, 7 and 14 days ( Figure 3E ). ALP is an important marker during early osteogenic differentiation [ 49 ], of which peak expressions generally appeared at 7 days. BMSCs cultured on FG Ti-P/pBMP2-6 showed a 1.3 and 1.9-fold enhanced expression of ALP compared to CG Ti-P/pBMP2-6 and uncoated FG Ti, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…We first identified SAIB as an effective excipient among the five compounds (Pluronic F127, Pluronic F68, Pluronic L31, and Span80) that were tested. SAIB has been used as a viscous injectable depot system for sustained drug release and elicited mild inflammation after intramuscular injection in rats. , However, its effectiveness as an excipient in PCL to sustain drug release has not been tested before. These five excipients all have shown surfactant properties and exhibited a wide range of hydrophilicity/hydrophobicity.…”
Section: Discussionmentioning
confidence: 99%